Bioremediation Greywater using Vermifilter - Ratnawati, Rhenny; Nurhayati, Indah; Sutrisno, Joko; Sugito, Sugito (Jurnal Rekayasa Kimia & Lingkungan, 2022)
Vermifilter is a greywater waste treatment by utilizing the symbiosis of earthworms with microbes. Vermifilter is more efficient, simple in design, and easy to maintain. The purpose of this study was to determine the effect of vermibed material on the concentration of BOD5, NH3-N, and DO in greywater waste treatment using vermifilter. The study used four vermifilter reactors (VF) with filtration media for gravel, coconut fiber, rough sand, and vermibed. Reactor VF1 uses a vermibed mixture of mustard greens and cabbage, VF2 sawdust, VF3 banana stalk, and VF4 cow dung. This study provides results that VF1 removal BOD5 90%, NH3-N 98%, and increase DO 164%; FV2 removal BOD5 92%, NH3-N 98%, and increase DO 185%; FV3 removal BOD5 94.5% NH3-N 98.5%, and increased DO 156%; and FV4 decreased BOD5 93%, NH3-N 99%, and increased DO 270%. The media material had no significant effect on the concentration of BOD, NH3-N, and DO.